2014
DOI: 10.1088/1054-660x/24/4/045801
|View full text |Cite
|
Sign up to set email alerts
|

Improved laser efficiency by direct diode laser pumping of the radiation-resistant Nd:gadolinium–scandium–gallium garnet

Abstract: Spectroscopic investigation of the radiation-resistant Nd:GSGG crystals and ceramics reported in this paper evidences that the absorption line at 883 nm corresponding to the unusual situation of quasi-degenerate absorption transitions 4 I 9/2 (2) → 4 F 3/2 (1) and 4 I 9/2 (3) → 4 F 3/2 (2) can be used for efficient direct diode laser pumping of this material, with stable absorption over an extended temperature range. It is inferred that the reduction of the quantum defect at this wavelength of pump compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The output powers obtained for each line and the wavelength of the transitions are in good agreement with the measured strength of emission cross-section values for the different transitions of the Nd ion in GSGG (Fig. 2, and [5,15]). Compared to earlier diode pumping results, the slope efficiencies obtained in this study are relatively low (22.6% in [5,15] versus 16% in this study for MMD diode pumping).…”
Section: B Continuous-wave Lasing Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The output powers obtained for each line and the wavelength of the transitions are in good agreement with the measured strength of emission cross-section values for the different transitions of the Nd ion in GSGG (Fig. 2, and [5,15]). Compared to earlier diode pumping results, the slope efficiencies obtained in this study are relatively low (22.6% in [5,15] versus 16% in this study for MMD diode pumping).…”
Section: B Continuous-wave Lasing Resultssupporting
confidence: 84%
“…2, and [5,15]). Compared to earlier diode pumping results, the slope efficiencies obtained in this study are relatively low (22.6% in [5,15] versus 16% in this study for MMD diode pumping). We suspected that this fact is due to the higher passive losses of the Cr:Nd:GSGG crystal that we have at hand during this study.…”
Section: B Continuous-wave Lasing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR luminescence was observed in chromium-doped GGG, and yellow persistent luminescence was determined in ceriumand chromium-co-doped GGG [39,40]. Improved physical properties were also observed for differently doped gadolinium scandium gallium garnets (Gd 3 Sc 2 Ga 3 O 12 , GSGG) [41][42][43]. The results reported in several studies [44][45][46][47] indicated that transition metal-or lanthanide-doped lutetium gallium garnets (Lu 3 Ga 5 O 12 , LuGG) are promising new laser materials, and they are expected to be comparable to the most widely used compound, YAG.…”
Section: Introductionmentioning
confidence: 95%
“…R 2 (884.4 nm) are collected in a two-peaked absorption band centered at 885 nm, with integral absorption similar to that of the Z 1 ? R 2 band and with $3 nm FWHM for 1 at.% Nd [31][32][33]; for Nd:GSGG these two absorption lines are practically coincident [34]. Pumping the Nd:YAG at 885 nm reduces the quantum defect by $9.5% and the heat load parameter for the one-micron laser emission by $30% compared with 808 nm pumping [31][32][33].…”
Section: Discussionmentioning
confidence: 89%